Development of slate fiber reinforced high density polyethylene composites for injection molding. (February 2015) - Carbonell-Verdú, A.; García-García, D.; Jordá, A.; Samper, M.D.; Balart, R.
Abstract: During the last decade the use of fiber reinforced composite materials has consolidated as an attracting alternative to traditional materials due to an excellent balance between mechanical properties and lightweight. One drawback related to the use of inorganic fibers such as those derived from siliceous materials is the relative low compatibility with conventional organic polymer matrices. Surface treatments with coupling agents and the use of copolymers allow increasing fiber–matrix interactions which has a positive effect on overall properties of composites. In this research work we report the use of slate fiber treated with different coupling agents as reinforcement for high density polyethylene from sugarcane. A silane (propyltrimethoxy silane; PTMS) and a graft copolymer (polyethylene-graft-maleic anhydride; PE- g -MA) were used to improve fiber–matrix interactions on HDPE-slate fiber. The effect of the different compatibilizing systems and slate fiber content were evaluated by scanning electron microscopy (SEM), dynamic thermomechanical analysis (DTMA) as well as mechanical properties (tensile, flexural and impact). The results show that the use of silane coupling agents leads to higher fiber–matrix interactions which has a positive effect on overall mechanical properties. Interesting results are obtained for composites containing 30 wt.% slate fiber previously treated with propyltrimethoxy silane (PTMS) with an increase in tensile and flexural strength of about 16% and 18% respectively.